Empirical social research in Germany, 1848-1914. [With pref. by P.F. Lazarsfeld] (Mouton, 1965)
With bibliogr. Publications of the International Social Science Council. Publ. with the assistance of the Bureau of Applied Social Research (Columbia University) and the Ecole pratique des hautes Etudes (Sorbonne).